DEVELOPMENT CULTURE-BASED LEARNING THROUGH AUDIOVISUAL MEDIA FOR PROSPECTIVE HISTORY TEACHERS AT TADULAKO UNIVERSITY - Juraid Abdul Latief; Iskandar Ahmad; Misnah Misnah; Mahfud Mahmud Gamar (Universitas Labuhanbatu, 2026)
Purpose – This study aims to design a culture-based learning model using audiovisual media to enhance historical understanding and pedagogical competence among prospective history teachers at Tadulako UniversityMethodology – The research employed a qualitative Research and Development (R&D) approach integrated with cyclical Classroom Action Research (CAR). The process consisted of five stages: needs analysis, design, development, implementation, and evaluation. Data were gathered through classroom observations, semi-structured interviews, and document analysis. The main outputs included short documentaries, narrative podcasts, microlearning videos, and digital archives rooted in Central Sulawesi’s local culture. Data were analyzed thematically and validated through triangulation and peer review.Findings – The results show that integrating audiovisual media into culture-based learning significantly improved students’ motivation, engagement, and historical thinking—particularly in evidence analysis, continuity and change, and perspective-taking. Authentic assessment confirmed that most student projects met standards of historical accuracy, multimedia coherence, and ethical cultural representation. Technical disparities were mitigated through peer mentoring, shared resources, and ethical consultation with local communities.Contribution – The study contributes theoretically by integrating culture-based learning, multimedia principles, and historical thinking into a contextual pedagogical framework. Practically, it enhances teacher candidates’ cultural, digital, and pedagogical literacy and offers a replicable model for history education innovation in resource-limited settings.